Plasma leptin responses to prolonged sculling in female rowers - Jürimäe, J.; Jürimäe, T. (The Journal of Sports Medicine and Physical Fitness, 2004)
Aim: Plasma leptin concentrations are reduced in the presence of a negative energy balance. The purpose of this study was to investigate the effects of a prolonged single endurance rowing training session on plasma leptin concentrations in female rowers. Methods: Ten female college level single scull rowers participa-ted in this study. Venous blood samples were obtained during the early follicular phase of the menstrual cycle immediately before and after on-water rowing lasting about 2 h (7518±293 s; distance covered 18.9±1.4 km; heart rate 150±7 beats . min-1). Results: Blood lactate concentration did not change significantly during sculling training session (from 1.6±0.4 to 1.9±0.5 mmol . l-1) indicating that training was performed at moderate intensities. Leptin values were significantly reduced immediately after prolonged rowing by a mean 44% and no further changes occurred during the first 2 h of recovery. Insulin and glucose values were also decreased immediately after prolonged rowing. A further reduction in insulin was seen during the 2nd hour of recovery. No further changes occurred during the first 2 h of recovery in glucose concentration. Plasma leptin concentrations immediately after (r=-0.64), and 30 min (r=-0.66) and 2 h (r=-0.64) after an endurance rowing training session were related (p<0.05) to the distance covered. No such relation was observed for other measured blood biochemical parameters. Leptin also correlated with insulin measured at different time points after endurance training (r>0.64; p<0.05). Regression analyses demonstrated a positive relationship between total body fat mass and plasma leptin (R2>0.70; p<0.001) regardless of sampling time in female rowers. Conclusion: Our findings indicate that a prolonged low-intensity rowing training session results in an energy deficit beyond the threshold that is necessary to reduce plasma leptin concentration without changing body fat mass in female rowers. It was suggested that plasma leptin could be regarded as a signal for metabolic reaction to endurance rowing training session and following recovery in female endurance athletes.